Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ \(A=\frac{cot^2a-cos^2a}{cot^2a}-\frac{sina.cosa}{cota}\)
\(=\frac{\frac{cos^2a}{sin^2a}-cos^2a}{\frac{cos^2a}{sin^2a}}-\frac{sina.cosa}{\frac{cosa}{sina}}\)
\(=\left(1-sin^2a\right)-sin^2a=1\)
b/ \(B=\left(cosa-sina\right)^2+\left(cosa+sina\right)^2+cos^4a-sin^4a-2cos^2a\)
\(=cos^2a-2cosa.sina+sin^2a+cos^2a+2cosa.sina+sin^2a+\left(cos^2a+sin^2a\right)\left(cos^2a-sin^2a\right)-2cos^2a\)
\(=2+\left(cos^2a-sin^2a\right)-2cos^2a\)
\(=2-sin^2a-cos^2a=2-1=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\frac{\cos57}{\cos57}+\frac{\cot58}{\cot58}-2\left(1+1\right)\)\()\)
=1+1-4
=-2
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có:
\(sin^2a+cos^2a=1\Leftrightarrow sin^2a+\left(\frac{1}{3}\right)^2=1\Leftrightarrow sin^2a=\frac{8}{9}\Rightarrow sina=\frac{2\sqrt{2}}{3}.\)
\(B=\frac{sin\alpha-3cosa}{sina+2cosa}=\frac{\frac{2\sqrt{2}}{3}-3.\frac{1}{3}}{\frac{2\sqrt{2}}{3}+2.\frac{1}{3}}=\frac{7-5\sqrt{2}}{2}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\sin^4\alpha+\cos^4\alpha=\left(\sin^2\alpha+\cos^2\alpha\right)^2-2\sin^2\alpha.\cos^2\alpha=1-2.\frac{1}{4^2}=\frac{7}{8}\)